Research on Teaching Reform of College Curriculum Based on Subject Knowledge Mapping Architecture - He, Lei; Wu, Yue (Applied mathematics and nonlinear sciences, 2024)
In this paper, we first construct a framework of subject knowledge mapping for teaching and learning reforms in higher education courses, automate the supervision of the proposed optimized CLSTM-GAT model for extracting and recognizing the texts of teaching and learning reforms in higher education courses using remote supervision, and propose a storage architecture for domain subgraphs to save storage space. The feasibility of the proposed model and architecture is evaluated through experiments. The visualization and analysis of the teaching reform of college courses based on the knowledge graph reveals that the frequency and centrality values of the subject term “teaching reform” in the research vocabulary are 10526 and 0.29, respectively, and that the value of the expansion coefficient of “local colleges and universities” is 17.5466. 17.5466, with 10 years, are the highest. In the research on teaching reform of college curriculum, the research theme words mainly center around keywords such as “teaching reform, colleges and universities, teaching mode”, and “local colleges and universities, reform practice and teaching reform” belong to the hot spot type of research direction in the future research on teaching reform of college curriculum. The research direction.